Characteristic emission from quantum dot-like intersection nodes of dislocations in GaN. Issue 1 (March 2021) - Shapenkov, S V; Vyvenko, O F; Schmidt, G; Bertram, F; Metzner, S; Veit, P; Christen, J
Abstract: Freshly introduced a-screw dislocations in gallium nitride are an effective source of ultraviolet radiation, characterized by intense emission of narrow luminescence doublet lines in the spectral range of 3.1-3.2 eV. Furthermore, an additional narrow spectral line with an energy of 3.3 eV has been found at the points of intersection of such dislocations, where extended dislocation nodes were formed. In this communication, we report on the spectral properties of the characteristic luminescence of such nodes, which were obtained for the (0001) gallium nitride samples with dislocations introduced by nanoindentation. The spectral position of the dislocation-related luminescence doublet experiences a redshift with increasing distance from the indentation site. It follows the spectral shift of the excitonic near-bandgap emission, associated with stress relaxation. The luminescence of the intersection points exhibits a similar tendency. At certain local positions, its doublet fine structure is observed, which has a spectral linewidth of the order of or even less than that of the exciton. In this case, the spectral splitting between components of the doublet varies irregularly depending on the position of the exciton (i.e., on the mechanical stress). We see a clear indication of quantum dot-like emission. The fine structure of the luminescence of the intersection points can be easily explained by the energy dependence of emission on their size, as well as on their density, in particular, by the formation of paired nodes, which were previously observed in experiments in a transmission electron microscope.